One Less Painful Procedure: Using Umbilical Cord Blood as Alternative Source to Admission Complete Blood Count - Prakash, Neera; Decristofaro, Joseph; Maduekwe, Echezona T. (American Journal of Perinatology, 2017)
Objective This study aims to evaluate the use of umbilical cord blood as an alternative to the admission complete blood count (CBC) in the well-appearing late preterm neonates admitted to the neonatal intensive care unit.Study Design Paired umbilical cord and admission blood CBC samples from well late preterm infants were compared using a two-sample t-test or analysis of variance with an unequal variance for differences in the hemoglobin, platelet counts, white blood cell, and absolute neutrophil counts.Results A total of 100 infants were enrolled in the study. The study included 46 females, 5 Asian, 9 Black, 35 Hispanic, 51 White, with a mean gestational age of 35.3 ± 1 weeks (range: 34–36.5 weeks), and a mean birth weight of 2,347 ± 491 g (range: 1,840–4,260 g). Around 80% were appropriate for gestational age, 5% were large for gestational age, and 15% were small for gestational age. The median difference between the cord and admission blood samples were hemoglobin: 1.1 g/dL, platelet: 7.50 × 103 cells/μL, white blood cell count: 2.3 × 103 cells/μL, and absolute neutrophil count: 0.6 × 103 cells/μL.Conclusion The cord and admission blood testing were not statistically or clinically different when compared. In well late preterm infants, the NICU admission blood CBC may be replaced with an umbilical cord blood CBC.
Keywords: cord blood; late preterm; infants; platelets; hemoglobin; leukocytes; pain